THE EFFECT OF VARIATION IN POLYPROPYLENE CONCENTRATION ADDED TO GONGGONG (Laevistrombus Canarium) SHELL POWDER COMPOSITE MATERIAL ON TENSILE STRENGTH CHARACATERISTICS AS A FILLER - Sari Rahmiati; Taufiq Rahman; Vitri Aprilla Handayani; Mulyono; Putriana Carona Manurung (Analit : Analytical and Environmental Chemistry, 2025)
The utilization of shell waste is often suboptimal, despite its potential as a composite filler material. This study aims to develop an environmentally friendly composite material based on gonggong shell powder combined with polypropylene. The research method involved the preparation of composite samples by mixing gonggong shell powder and polypropylene at various concentrations, followed by specimen fabrication using the hot press molding method. The resulting specimens were mechanically characterized through tensile testing based on the ASTM D638 standard, and the data were statistically analyzed using ANOVA to determine the significance of differences among composition variations. The research stages included observation, shell waste collection, cleaning, sterilization using NaOH solution, drying, grinding, and sieving to obtain fine powder. XRF analysis showed that gonggong shells are predominantly composed of calcium oxide (65.108%), indicating a high calcium carbonate content and strong potential as a composite filler. Tensile test results for specimens with polypropylene variations of 2.5%, 5%, 7.5%, and 10% revealed statistically significant differences (p < 0.05), with the optimal tensile strength of 35.03 MPa achieved at 5% concentration. These findings demonstrate that the developed composite material based on gonggong shell powder and polypropylene has strong potential as an environmentally friendly filler material with competitive mechanical properties.